a) [tex]\frac{5}{x}-\frac{y}{3}=\frac{1}{6}\Leftrightarrow \frac{5}{x}=\frac{1}{6}+\frac{y}{3}\Leftrightarrow \frac{5}{x}=\frac{2y+1}{6}\Rightarrow x(2y+1)=30[/tex]
Vì x, y là số tự nhiên nên: [tex]2y+1\geq 1[/tex]. Mặt khác 2y+1 là số lẻ nên [tex]2y+1\in \left \{ 1;3;5;15 \right \}\Rightarrow y\in \left \{ 0;1;2;7 \right \}\\ \Rightarrow x\in \left \{ 30;10;6;2 \right \}[/tex]
b) [tex]\frac{4}{x}-\frac{y}{3}=\frac{5}{6}\Leftrightarrow \frac{4}{x}=\frac{5}{6}+\frac{y}{3}=\frac{5+2y}{6}\Rightarrow 24=x(5+2y)[/tex]
Đến đây làm tương tự như câu a